Electronic memory aids for people with dementia experiencing prospective memory loss: A review of empirical studies. (August 2019) - King, Alexandra C; Dwan, Corinna
This paper details a review of the literature on the use of electronic aids for prospective memory for people with dementia. Key findings of the review are that: electronic memory aids show potential for supporting people's prospective memory but the devices and software applications need further development in order to function reliably; sample sizes of studies are often very small, limiting the generalisability of their findings; few studies of devices are conducted in users' home environments; and most of the studies focus on the effectiveness of the electronic memory aid, rather than outcomes for users, such as improved daily functioning, quality of life, or social connectedness. The review concludes that future studies with robust devices are required that explicitly focus on the varying needs and capacities of people with dementia, in order to generate additional evidence for the effectiveness of electronic memory aids for this cohort.